Electronic Electronic Customer Relationship Management Menggunakan Framework Codeigniter dengan Metode Waterfall Berbasis Website - Yudhi Setiawan; Iskandar Fitri; Ira Diana Sholihatih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
E-commerce or online stores appear to provide convenience for the public in the field of information technology, Budi Luhur is a shop in the field of selling household needs such as cabinets, plate racks, spring beds, sofas, and electronics. But the problem is that until now, how to market their products still using manuals such as brochures, posters, and orders that are still recorded manually with books, so that the store requires costs that are sometimes not small in number to print brochures which will later be used to convey information to customers manually. To overcome these problems, it is necessary to create a system at the Budi Luhur store that can make it easier for customers and shop owners to make transactions. The design of Budi Luhur's E-Commerce System uses a Software development methodology, namely the waterfall method. This method is used by researchers to develop Software systems by having a Software life flow sequentially starting from analysis, design, coding and testing. To design the system using E-CRM (Electronic Electronic Customer Relationship Management), CodeIgniter Framework, PHP programming language and MySQL database.